Social Commerce and the Rise of Halal Beauty: Investigating the Drivers of Muslim Consumer's Purchase Intention - Inayah Khoirunnisa Hariyadi; Nabila Kharimah Vedy (Universitas KH. Abdul Chalim Mojokerto, 2025)
Social commerce is a sales platform that involves social media, to create social interactions with consumers, one of which is TikTok Shop. This study aims to analyze the effect of perceived trust, the TAM model (attitude, perceived ease of use, and perceived usefulness), and alternative evaluation on purchase intention on beauty products through TikTok Shop for Muslim consumers in Indonesia. This research uses a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis technique. The sample consisted of 272 respondents, and only 163 data were processed after meeting the criteria. The analysis results show that perceived trust, attitude, perceived usefulness, and alternative evaluation have a positive and significant effect on purchase intention. In contrast, perceived ease of use has no significant effect on purchase intention, although it has a significant relationship with perceived usefulness. These findings confirm the importance of trust, attitude, perceived usefulness, alternative evaluation in shaping consumer purchase intention.